Pengaruh Kualitas Produk, Inovasi dan Diferensiasi Produk Terhadap Minat Beli Konsumen Pada Sentra Wisata Kuliner Dharmawangsa Surabaya - Mufadilah, Siti Bakhriyatul (Research Journal of Social Science and Economics, 2025)
The city of Surabaya is one of the cities that provides or provides opportunities for street vendors in the Surabaya area. Culinary Tourism Center is a solution to drive the wheels of the people’s economy. Even though there are still many obstacles, this effort raises great hopes for the Culinary Wiata Center traders. Through this culinary tourism center, it is hoped that business actors will be able to develop the creativity of the culinary sector and be able to attract local and foreign tourists. The aim of this study was to determine the effect of product quality, innovation and product differentiation on consumer buying interest at the Dharmawangsa Culinary Tourism Center. This type of research is field research, namely direct observation of the object under study in order to obtain relevant data. The method used in this research is to use quantitative research methods. The population taken was in the form of consumers of the Dharmawangsa Surabaya Culinary Tourism Center as many as 100 respondents. The data collection technique in this study was using a google form/distribution of questionnaires. Based on the results of this study, it proves that product quality has no significant effect on consumer buying interest at the Dharmawangsa Culinary Tourism Center, while Product Innovation and Product Differentiation have a significant effect on Consumer Purchase Interest at the Dharmawangsa Culinary Tourism Center. Based on the results of this study indicate that Product Quality, Product Innovation and Product Differentiation have a joint effect on Consumer Purchase Interest at the Dharmawangsa Culinary Tourism Center. Keywords: Product Quality, Product Innovation, Product Differentiation, Consumer Purchase Interest.